Religious life in Normandy, 1050-1300: space, gender, and social pressure - Hicks, Leonie V. (Boydell & Brewer, 2007)
'A vivid and absorbing picture both of the internal workings of religious houses in Normandy and their interactions with a wider society.' Professor ANN WILLIAMS. The religious life was central to Norman society in the middle ages. Professed religious and the clergy did not and could not live in isolation; the support of the laity was vital to their existence. How these different groups used sacred space was central to this relationship. Here, fascinating new light is shed on the reality of religious life in Normandy. The author uses ideas about space and gender to examine the social pressures arising from such interaction around four main themes: display, reception and intrusion, enclosure and the family. The study is grounded in the discussion of a wide range of sources, including architecture, chronicles and visitation records, from communities of monks and nuns, hospitals and the parish, allowing the people, rather than the institutions, to come to the fore. Dr LEONIE V. HICKS teaches at the University of Southampton.